Development of the Tonsil Microbiome in Pigs and Effects of Stress on the Microbiome - Pena Cortes, Luis Carlos; LeVeque, Rhiannon M.; Funk, Julie A.; Marsh, Terence L.; Mulks, Martha H. (Frontiers in Veterinary Science, 2018)
Tonsils, lympho-epithelial tissues located at the junction of the oropharynx and nasopharynx, play a key role in surveillance, colonization, and persistence of inhaled and ingested pathogens. In pigs, the tonsils are a reservoir for numerous bacteria and viruses, including host-specific pathogens and potential zoonotic pathogens as well as commensal organisms. However, there are no in depth studies of the development of the tonsillar microbiome in pigs, or any mammal, over time. The goal of this study was to follow the development of the tonsil microbiome in healthy pigs from birth to market weight. Samples were collected using tonsil brushes from 16 piglets (4 each from 4 sows) at newborn, 1, 2, 3 and 4 weeks of age, and from 8 of those piglets at 6, 8, 10, 12, 16 and 19 weeks of age. Bacterial DNA was isolated from each sample and 16S rDNA genes were amplified and sequenced. Sequence analysis showed that members of the Streptococcaceae, Pasteurellaceae and Moraxellaceae were present at all time points and represent the three most abundant families identified. Other community members appeared transiently or increased or decreased significantly with disruption events or stress. We observed four significant shifts in the tonsil community that coincided with well-defined disruption events: weaning plus addition of Carbadox plus movement to the nursery at week 3, removal of Carbadox and addition of Tylan at week 5, removal of Tylan and habitat change at week 9, and habitat change at week 16. Weaning triggered a bloom of Streptococcaeae and decrease of Moraxellaceae. The shift from Carbadox to Tylan led to reduction in Proteobacteria and Streptococcaceae but an increase in other Firmicutes, accompanied by a dramatic increase in community richness. Cessation of Tylan coincided with a return to a less rich community, and a bloom in Clostridiales. The final shift in habitat was accompanied by a decrease in Clostridiales and increase in Proteobacteria. The tonsillar microbiome of older pigs resembled the previously described mature core tonsillar microbiome. This study demonstrates a temporal succession in the development of the pig tonsillar microbiome, and significant community shifts that correlate with disruption events.